High‐Performance Upscaled Indium Tin Oxide–Free Organic Solar Cells with Visual Esthetics and Flexibility. Issue 9 (14th July 2021) - Zhao, Feng; Zuo, Lijian; Li, Yaokai; Zhan, Lingling; Li, Shuixing; Li, Xin; Xia, Ruoxi; Yip, Hin–Lap; Chen, Hongzheng
Abstract : Organic solar cells (OSCs) show great promise for future applications due to their merits of low cost, flexibility, and vivid colors, etc. However, the "conventional" device architecture with a brittle and expensive glass/indium tin oxide (ITO) transparent electrode weakens these potential advantages and restricts it to small areas for high performance. Herein, a device architecture simultaneously combining the advantages of high performance, superior flexibility, diverse colors, and low‐cost upscaling production is developed. The device structure features a top‐illumination geometry with a thermally evaporated ultrathin Ag film as transparent electrode for ITO replacement. The formation of optical microcavity and high conductance of ultrathin Ag enables high performance for upscaled OSCs. Moreover, this device architecture further enables diverse colors via tuning the TeO2 layer atop of the ultrathin Ag transparent electrode. This top‐illumination structure is more tolerant for substrates and enables wider flexible substrates. As a result, the flexible OSCs with upscaled areas of 1.05 cm 2 exhibit a best performance of 13.09% (certified 11.9%) with superior flexibility, diverse colors, representing one of the best ITO‐free upscaled flexible OSCs. This work provides a versatile device structure to highlight the merits of OSCs, and paves the way for the future commercialization and practical applications. Abstract : High‐performance 1.05 cm 2 flexible organic solar cells (OSCs) with top‐illumination device structure and ultrathin Ag as transparent electrode are demonstrated. This structure simultaneously combines the advantages of high performance, superior flexibility, diverse colors, and low‐cost upscaling of production, and the corresponding OSCs deliver the maximum power conversion efficiency of 13.09%, representing one of the best among upscaled flexible OSCs.